Precarious work and the reluctance to complain: Italian temporary migrant workers in Australia. (2nd January 2019) - Campbell, Iain; Tranfaglia, Maria Azzurra; Tham, Joo-Cheong; Boese, Martina
ABSTRACT: The reluctance of many temporary migrant workers (TMWs) to challenge poor wages and conditions is an important puzzle for both research and policy. This article explores the puzzle by drawing on in-depth interviews with Italian TMWs who have had recent work experience in food services and/or farms in Australia. The article describes their experiences of precarious work, marked by widespread and systematic underpayment of wages in breach of minimum wage regulation. It shows that few Italian TMWs challenged underpayments, whether through collective or individual action. The article reviews the varied rationales offered by the interviewees for their reluctance to pursue an individual complaint about underpayments. It finds that fear of employer reprisals was a powerful and understandable barrier to action. Also influential, however, were attitudes that had the effect of downplaying the significance of low pay in the current job, for example, by means of a judgment that the current job is only a temporary stage in a long-term life-course project. The findings indicate that reluctance to complain needs to be situated in relation to other forms of migrant worker agency, both within and outside the workplace, and the social relations in which they are embedded.